1999
DOI: 10.1017/s0954579499002357
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors in substance use: A study of suburban and inner-city adolescents

Abstract: Objectives in this research were to examine contextual differences in correlates of substance use among high school students. The focus was on two broad categories of adjustment indices: personal psychopathology (internalizing and externalizing problems) and behaviors reflecting social competence (academic achievement, teacher-rated classroom behaviors, and peer acceptance or rejection). Associations between drug use and each of these constructs were examined in two sociodemographically disparate groups: teens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
213
6
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(258 citation statements)
references
References 80 publications
34
213
6
1
Order By: Relevance
“…By the 12th grade, on the other hand, high-SES youth reported the highest rate of several drugs, including marijuana, inhalants, and tranquilizers. Regarding correlates of drug use, Way, Stauber, Nakkula, and London (1994) found, as did Luthar and D'Avanzo (1999), that high-SES youth (but not their inner-city counterparts) often used substances in efforts to alleviate emotional distress. Similarly, Cooper (1994) noted that among adolescent boys in general, more so than girls, alcohol use is often tied to social conformity motives such as drinking to fit in with a crowd, and Feldman, Rosenthal, Brown, and Canning (1995) showed that popular preadolescent boys were among those most prone to partying and heavy drinking later as high school students.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…By the 12th grade, on the other hand, high-SES youth reported the highest rate of several drugs, including marijuana, inhalants, and tranquilizers. Regarding correlates of drug use, Way, Stauber, Nakkula, and London (1994) found, as did Luthar and D'Avanzo (1999), that high-SES youth (but not their inner-city counterparts) often used substances in efforts to alleviate emotional distress. Similarly, Cooper (1994) noted that among adolescent boys in general, more so than girls, alcohol use is often tied to social conformity motives such as drinking to fit in with a crowd, and Feldman, Rosenthal, Brown, and Canning (1995) showed that popular preadolescent boys were among those most prone to partying and heavy drinking later as high school students.…”
mentioning
confidence: 90%
“…Second, findings suggested that the teenage peer group might actively endorse substance use among suburban boys. High substance use was linked to their popularity with peers, and this association remained significant despite statistical controls in regression equations for various possible confounds, including both internalizing and externalizing problems (Luthar & D'Avanzo, 1999).…”
mentioning
confidence: 97%
See 3 more Smart Citations